Леся Українка в пізніх інтерпретаціях Дмитра Донцова: націософський і культурологічний континууми - Баган, Олег; Bahan, Oleh (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано два есеї Д. Донцова про драматичні твори Лесі Українки «Три хвилини», «Адвокат Мартіян». Автор доводить, що ідеологічно письменниця виражала в художніх формах консервативні, ідеалістичні й ірраціоналістичні струмені в українській культурі початку ХХ ст. Обидва твори мають чітку націософську проблематику, утверджують принципи історичного волюнтаризму, національного героїзму та революціонізму як емоційно-протест- ної енергетики буття. ter Interpretations of Dmytro Dontsov: Natiosophical and Cultural Continuum. In this article it is analyzed two essays of Dmytro Dontsov about the dramatic works of Lesia Ukrainka “Three Minutes” and “Lawyer Martiyan”. The author proves that ideologically writer expressed in artistic forms the conservative and idealistic irratsional streams in Ukrainian culture in the early twentieth century. It is explained that it was almost the only author in the Ukrainian literature of that time, who wrote in a such philosophical way. The cause for this was the neo-romantic worldview of Lesia Ukrainka, her individual and heroic spirits. At the same time it is granted attention to the evolution of the outlook of Dmytro Dontsov as the most brilliant Ukrainian theorist of traditionalism and philosophical irrationalism in the article. It is granted the main attention to the analysis of the ideological concepts of Lesіa Ukrainka in these dramatic poems, which concentrated her main political views on the modern history of Ukraine in itself. Both works have a clear natsiosofski problems, affirm the principles of historic voluntarism, national heroism and revolutionism as emotional and protest energy of being.
Lesia Ukrainka in Later Interpretations of Dmytro Dontsov: Natiosophical and Cultural Continuum
Keywords: націософія; ірраціоналізм; ідеалізм; волюнтаризм; героїзм; неоромантизм; консерватизм; традиціоналізм; natiosophy; irrationalism; idealism; voluntarism; heroism; conservatism; neoromanticism; traditionalism